Doublespeak in the Public Statements of Indonesia's Public Officials: A Post-truth Phenomenon - Muhammad Akbar Dermawan; Ribut Basuki (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
Doublespeak is a form of linguistic manipulation frequently employed by public officials to obscure truth, evade accountability, and distort reality. In the current post-truth era, where objective facts are often subordinate to political agendas and personal beliefs, this phenomenon has become increasingly prevalent in Indonesia. This article examines the use of doublespeak by Indonesian public officials in mass media statements and analyzes its relationship with the concept of post-truth and power dynamics. Using a schema of language analysis, this study investigates news coverage from major online media platforms regarding critical cases, including the Nusantara Capital City (IKN) project, the Rempang conflict, and the COVID-19 pandemic. The findings demonstrate that officials utilize various forms of doublespeak—primarily euphemism, jargon, and inflated language—to deny scientific evidence, shift responsibility, and frame political narratives. The study concludes that in Indonesia’s contemporary political landscape, doublespeak functions not merely as a rhetorical strategy but as a mechanism of governmentality designed to regulate societal behavior and maintain ideological supremacy in a society increasingly indifferent to absolute truth.